Leaf protein allocation across the canopy and during senescence in earlier and later senescing maize hybrids, and implications for the use of chlorophyll as a proxy of leaf N - Antonietta, Mariana; Giron, Paula; Costa, María Lorenza; Guiamet, Juan José (Springer, 2019)
Leaf chlorophyll (chl) and protein distribution were analyzed throughout grain filling in four modern maize hybrids with contrasting senescence behavior, at three different canopy levels and at low-N (LN, 18 kg N ha−1) and high-N (HN, 218 kg N ha−1) fertilization levels. Chl content assessed by SPAD resembled protein content only at LN, with delayed senescing genotypes having more leaf protein content than reference genotypes. Across N levels, relative chl content negatively related to light intensity (r2 = 0.59, P < 0.001), while relative protein content did only for the lowest part of the canopy (r2 = 0.54, P < 0.001), suggesting protein distribution in the canopy could be further improved. Relative Rubisco/LHCII partitioning increased from lower to upper leaves (P < 0.09) and differed among genotypes (P < 0.05) with no link to senescence behavior. Photosynthetic electron transport rates were lower at LN and differed between genotypes (P < 0.05) including those with similar leaf protein contents. Chl and protein contents were related across the entire dataset (r2 = 0.53, P < 0.001) but the slope (b) of this relationship varied widely depending on the leaf position (b = 0.026–0.019), the senescence stage (b = 0.014–0.020), the N level (b = 0.035–0.026) and the hybrid (b = 0.016–0.033). Our results suggest that in modern maize hybrids, leaf N utilization can be further improved and that genotypic together with other sources of variation should be included as specific variables in SPAD-based predictions of leaf N content.